A polyester catalyst and its preparation method and application

The novel polyester catalyst prepared by microhydrolysis-substitution-curing method solves the problem of difficult control of the hue of the titanate catalyst and easy hydrolysis, and realizes the preparation of PBT slices with low hue.

CN114479040BActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202011154925.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-10-26
Publication Date
2025-03-04
Estimated Expiration
2040-10-26

AI Technical Summary

Technical Problem

When titanate is used as a polyester catalyst in the prior art, the hue of the product is difficult to control, and the catalyst is easy to hydrolyze, affecting the hue and quality of the product.

Method used

A novel polyester catalyst is prepared by microhydrolysis-substitution-curing method, which includes reaction products of diols, water, titanium compounds, metal compounds, organic acids and phosphates, and the PBT sections prepared by the catalyst have a low hue.

Benefits of technology

While maintaining the catalytic activity unchanged, the color of the PBT sections prepared by the catalyst is lower than that prepared with tetrabutyl titanate, and better technical results are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002742472560000161
    Figure BDA0002742472560000161
Patent Text Reader

Abstract

The present invention discloses a polyester catalyst and a preparation method and application thereof. The polyester catalyst comprises a reaction product of the following substances: diol, water, titanium compound, optional metal compound, organic acid and phosphate. The metal compound can be added during the preparation of the catalyst or during the later preparation of polyester. The catalytic activity of the catalyst prepared by the method of the present invention is maintained to be equivalent to that of tetrabutyl titanate. The PBT slices prepared by the catalyst have a much lower hue than the slices prepared by tetrabutyl titanate, and the catalyst is resistant to hydrolysis, thereby achieving a good technical effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, in particular to a polyester catalyst, and specifically to a polyester catalyst and a preparation method and application thereof. Background Art

[0002] Polybutylene terephthalate (PBT) is a crystalline linear saturated polyester and a thermoplastic material. Due to its easy processing and excellent electrical, mechanical and heat resistance properties, it is widely used in electronic and electrical components, automobiles, mechanical equipment, optical cables and optical fibers. It is also gradually being widely used in films, sheets, fibers and other fields.

[0003] With the advancement of science and technology and the improvement of quality of life, many application fields have put forward higher requirements for the color of PBT. PBT is different from PET. PBT mostly uses tetrabutyl titanate (TBT) as a catalyst, while PET mostly uses antimony acetate or ethylene glycol antimony as a catalyst. Due to the activity of titanium itself, the color of the product is difficult to control, and it is difficult to make too much change in the form of process adjustment in the existing technology. At the same time, tetrabutyl titanate is easy to hydrolyze, and the generated hydrolysis products are not only easy to accumulate on the wall of the vessel, affecting heat transfer, but also affecting the color quality of the product. Other titanium salts such as the hydrolysis products of titanium oxalate, titanium tetrachloride, and titanium sulfate have poor solubility in butanediol and are not suitable for the production of PBT.

[0004] Patent CN101824143A discloses a method for preparing highly crystalline thermoplastic polybutylene terephthalate, wherein tetrabutyl titanate and nano titanium dioxide solution are used as catalysts, and talcum powder and cobalt acetate are added to react to obtain the product. PBT crystallizes quickly, but the catalyst is still prone to hydrolysis.

[0005] Patent CN101253217A discloses a catalyst for preparing PBT using a titanium compound and a compound of an element from Group 1 and Group 2 of the periodic table, but the titanium compound is not resistant to hydrolysis and is easily deactivated.

[0006] Patent CN1720216C discloses a catalyst composition, including an alcohol salt of titanium, zirconium, hafnium or lanthanide metal, and a reaction product with a diol, 2-hydroxycarboxylic acid and a base. However, although the color b value of the product in the patent is low, the L value is also greatly reduced, which does not meet the actual production needs.

[0007] Patent CN105085873A discloses a continuous catalytic production method for PBT resin, in which a traditional Ti(OR)4 alkoxy titanium catalyst is reacted with 1,4-butanediol to obtain a diol titanium catalyst containing at least one alkoxy group substituted by 1,4-butanediol to participate in the continuous reaction of PBT resin, but no specific product indicators are mentioned. Summary of the invention

[0008] The present invention aims to solve the problem that the hue of polyester products is difficult to reduce due to the use of titanate in the prior art and the catalyst is easily hydrolyzed. The present invention provides a new polyester catalyst, whose catalytic activity is maintained at the same level as that of tetrabutyl titanate. The PBT slices prepared by the catalyst have a much lower hue than the slices prepared by tetrabutyl titanate, thereby achieving a better technical effect.

[0009] One of the objects of the present invention is to provide a polyester catalyst, which comprises a reaction product of a diol, water, a titanium compound, an optional metal compound, an organic acid and a phosphoric acid ester. Preferably, the catalyst comprises a reaction product of: (1) a reactant I of a diol, water, a titanium compound and an optional metal compound; (2) an organic acid; (3) an optional metal compound; and (4) a phosphoric acid ester.

[0010] The metal compound can be added during the preparation of the catalyst or during the later preparation of the polyester. Specifically, the metal compound can be added together with the diol, water and titanium compound during the preparation of the reactant I, or can be added together with the organic acid and phosphate ester during the preparation of the catalyst after the reactant I is obtained, or can be added together with the polyester raw material during the polyester synthesis process after the reactant I, the organic acid and the phosphate ester react.

[0011] In a preferred embodiment, the diol is selected from C2 to C 10 of dihydric organic alcohols.

[0012] In a further preferred embodiment, the dihydric alcohol is selected from C2-C8 (eg C2-C5) dihydric organic alcohols.

[0013] The dihydric organic alcohol refers to an organic alcohol containing two hydroxyl groups.

[0014] In a further preferred embodiment, the diol is at least one selected from 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, pentanediol, ethylene glycol, 1,6-hexanediol, 1,4-cyclohexanedimethanol and diethylene glycol.

[0015] Most preferably, the diol is selected from the diol raw material used in polyester synthesis, that is, the diol used in preparing the catalyst is consistent with the diol monomer raw material used in the subsequent polyester polymerization.

[0016] The catalyst has very good miscibility with water and diols and can be added at any time during the polyester polymerization process.

[0017] In a preferred embodiment, based on 100 wt% of the total weight of the diol and water, the amount of water used is 0.1 wt% to 10 wt%, preferably 0.1 wt% to 5 wt%.

[0018] Among them, water and diol can be mixed first to obtain water-containing diol, and then mixed with the titanium compound; water can also be added to the mixed solution of diol and titanium compound.

[0019] In a preferred embodiment, the titanium compound is selected from alkoxy titanate, represented by Ti(OR)4, wherein R is selected from C1 to C 10 A straight chain or branched hydrocarbon group.

[0020] In a further preferred embodiment, the titanium compound is Ti(OR)4, wherein R is a straight chain or branched hydrocarbon group selected from C1 to C8.

[0021] In a further preferred embodiment, the titanium compound is at least one selected from tetramethyl titanate, tetraethyl titanate, tetraethylhexyl titanate, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, and tetraisooctyl titanate.

[0022] In a preferred embodiment, the molar ratio of the diol to the titanium compound is (1-15):1.

[0023] In a further preferred embodiment, the molar ratio of the diol to the titanium compound is (5-12):1.

[0024] In a preferred embodiment, reactant I is obtained at 40-100°C.

[0025] In a further preferred embodiment, reactant I is obtained at 50-80°C.

[0026] Among them, the main reason why alkoxy titanate is afraid of water is that the titanium oxide ester bond is easily attacked by strong polar substances with hydroxyl groups such as water and some alcohols to form precipitation. Therefore, it is necessary to replace the bond position of the titanium-alkoxy bond in the titanate and solidify the molecule.

[0027] The present invention adopts a micro-hydrolysis-replacement-solidification method to prepare the catalyst. First, the titanate is micro-hydrolyzed, and the alkoxy group is partially replaced in a state containing a large amount of alcohol solvent, and then an organic acid, a metal compound and an organic phosphate are added to solidify the molecule, and finally a homogeneous catalyst is obtained, which can effectively avoid the attack of water on the catalyst structure. The diol mainly plays the role of solvent slow release and substitution group in the catalyst preparation. In addition, the proportion of water in the diol cannot be too high>10%, otherwise it will cause system gelation or even precipitation, and the proportion of water cannot be too low<0.01%, otherwise the purpose of micro-hydrolysis cannot be achieved.

[0028] In a preferred embodiment, the organic acid is selected from aliphatic organic acids and / or aromatic organic acids.

[0029] In a further preferred embodiment, the organic acid is selected from at least one (or at least two) of tartaric acid, oxalic acid, malic acid, citric acid, salicylic acid, lactic acid, and glycolic acid, preferably lactic acid and / or citric acid.

[0030] In a further preferred embodiment, the molar ratio of the organic acid to the titanium compound is (0.1-18):1, preferably (0.1-5):1, and more preferably (0.5-3):1.

[0031] In a preferred embodiment, the metal compound is selected from at least one of compounds containing Group IA elements, compounds containing Group IIA elements, compounds containing Group IIIA elements, and compounds containing Group IVA elements; preferably at least one of sodium-containing compounds, lithium-containing compounds, calcium-containing compounds, aluminum-containing compounds, germanium-containing compounds, and tin-containing compounds.

[0032] In a further preferred embodiment, the metal compound is selected from at least one (or at least two) of sodium acetate, potassium acetate, magnesium acetate, lithium acetate, calcium acetate, aluminum acetate, aluminum chloride, germanium dioxide, germanium hydroxide, stannous oxalate, and stannous octoate.

[0033] In a further preferred embodiment, the molar ratio of the metal compound to the titanium compound is (0-2):1, preferably (0.01-1):1.

[0034] In a preferred embodiment, the phosphate ester is selected from organic phosphate esters.

[0035] In a further preferred embodiment, the phosphate ester is selected from at least one (or at least two) of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate and triphenyl phosphate.

[0036] Among them, the phosphate ester can be used as a raw material for preparing the catalyst to react with reactant I, organic acid and metal compound to obtain the catalyst, or it can be directly added together with the polyester raw material during the polyester synthesis process.

[0037] In a further preferred embodiment, the molar ratio of the phosphate ester to the titanium compound is (0.1-4):1, preferably (0.1-2):1, and more preferably (0.1-1):1.

[0038] In a preferred embodiment, the reactant I, the organic acid, the optional metal compound and the phosphate ester are reacted at 10 to 100° C. for 0.5 to 10 hours to obtain the catalyst.

[0039] In a further preferred embodiment, reactant I, an organic acid, an optional metal compound and a phosphate are reacted at 10 to 90° C. (or preferably 60 to 100° C., such as 70° C., 80° C., 90° C.) for 2 to 6 hours to obtain the catalyst.

[0040] Wherein, the catalyst is a homogeneous liquid titanium polyester catalyst.

[0041] The second object of the present invention is to provide a method for preparing the polyester catalyst described in the first object of the present invention, comprising: mixing materials including a diol, water, a titanium compound, an optional metal compound, an organic acid and a phosphate ester, and obtaining the polyester catalyst through reaction.

[0042] In the above, the optional metal compound means that the metal compound may or may not be added.

[0043] Preferably, raw materials including the following components (1) to (4) are mixed and reacted to obtain the polyester catalyst: (1) reactant I of diol, water, titanium compound, and optional metal compound; (2) organic acid; (3) optional metal compound; (4) phosphate ester.

[0044] Among them, the metal compound can be added together with the diol, water, and titanium compound when preparing the reactant I, or it can be added together with the organic acid and phosphate ester when preparing the catalyst after obtaining the reactant I, or it can be added together with the polyester raw material during the polyester synthesis process after the reactant I, organic acid and phosphate ester react.

[0045] In a preferred embodiment, the diol is selected from C2 to C 10 of dihydric organic alcohols.

[0046] In a further preferred embodiment, the dihydric alcohol is selected from C2 to C8 (eg C5) dihydric organic alcohols.

[0047] In a further preferred embodiment, the diol is at least one selected from 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, pentanediol, ethylene glycol, 1,6-hexanediol, 1,4-cyclohexanedimethanol and diethylene glycol.

[0048] Most preferably, the diol is selected from the diol raw material used in polyester synthesis, that is, the diol used in preparing the catalyst is consistent with the diol monomer raw material used in the subsequent polyester polymerization.

[0049] The catalyst has very good miscibility with water and diols and can be added at any time during the polyester polymerization process.

[0050] In a preferred embodiment, based on 100 wt% of the total weight of the diol and water, the amount of water used is 0.1 wt% to 10 wt%, preferably 0.1 wt% to 5 wt%.

[0051] Among them, water and diol can be mixed first to obtain water-containing diol, and then mixed with the titanium compound; water can also be added to the mixed solution of diol and titanium compound.

[0052] In a preferred embodiment, the titanium compound is selected from alkoxy titanate, represented by Ti(OR)4, wherein R is selected from C1 to C 10 A straight chain or branched hydrocarbon group.

[0053] In a further preferred embodiment, the titanium compound is Ti(OR)4, wherein R is a straight chain or branched hydrocarbon group selected from C1 to C8.

[0054] In a further preferred embodiment, the titanium compound is at least one selected from tetramethyl titanate, tetraethyl titanate, tetraethylhexyl titanate, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, and tetraisooctyl titanate.

[0055] In a preferred embodiment, the molar ratio of the diol to the titanium compound is (1-15):1.

[0056] In a further preferred embodiment, the molar ratio of the diol to the titanium compound is (5-12):1.

[0057] In a preferred embodiment, the organic acid is selected from aliphatic organic acids and / or aromatic organic acids.

[0058] In a further preferred embodiment, the organic acid is selected from at least one (or at least two) of tartaric acid, oxalic acid, malic acid, citric acid, salicylic acid, lactic acid, and glycolic acid, preferably lactic acid and / or citric acid.

[0059] In a further preferred embodiment, the molar ratio of the organic acid to the titanium compound is (0.1-18):1, preferably (0.1-5):1.

[0060] In a preferred embodiment, the metal compound is selected from at least one of compounds containing Group IA elements, compounds containing Group IIA elements, compounds containing Group IIIA elements, and compounds containing Group IVA elements; preferably at least one of sodium-containing compounds, lithium-containing compounds, calcium-containing compounds, aluminum-containing compounds, germanium-containing compounds, and tin-containing compounds.

[0061] In a further preferred embodiment, the metal compound is selected from at least one (or at least two) of sodium acetate, potassium acetate, magnesium acetate, lithium acetate, calcium acetate, aluminum acetate, aluminum chloride, germanium dioxide, germanium hydroxide, stannous oxalate, and stannous octoate.

[0062] In a further preferred embodiment, the molar ratio of the metal compound to the titanium compound is (0.01-2):1, preferably (0.01-1):1.

[0063] In a preferred embodiment, the phosphate ester is selected from organic phosphate esters.

[0064] In a further preferred embodiment, the phosphate ester is selected from at least one (or at least two) of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate or triphenyl phosphate.

[0065] Among them, the phosphate ester can be used as a raw material for preparing the catalyst to react with reactant I, organic acid and metal compound to obtain the catalyst, or it can be directly added together with the polyester raw material during the polyester synthesis process.

[0066] In a further preferred embodiment, the molar ratio of the phosphate ester to the titanium compound is (0.1-4):1, preferably (0.1-2):1.

[0067] In a preferred embodiment, the preparation method comprises the following steps:

[0068] Step 1, mixing the diol, water, the titanium compound and the optional metal compound to obtain reactant I;

[0069] Step 2, mixing the obtained reactant I with the organic acid and the optional metal compound to obtain reactant II through reaction;

[0070] Step 3: mixing the obtained reactant II with the phosphate ester to obtain the polyester catalyst through reaction.

[0071] Preferably, the metal compound is added in step 1 and / or step 2.

[0072] In a preferred embodiment, step 1 is carried out at 40-100°C, preferably 50-80°C.

[0073] In a preferred embodiment, step 2 is carried out at 10-100° C. for 0.5-10 hours, preferably, at 10-90° C. (preferably 60-90° C.) for 2-6 hours.

[0074] The temperature of step 3 does not need to be strictly controlled and can be carried out under the residual heat of the reaction of step 2.

[0075] The third object of the present invention is to provide the use of the polyester catalyst described in the first object of the present invention or the polyester catalyst obtained by the preparation method described in the second object of the present invention in the preparation of polyester, especially for use in low-color polybutylene terephthalate resin.

[0076] A fourth object of the present invention is to provide a method for preparing polyester, the method comprising: using a dibasic acid and a diol as raw materials, and carrying out the process in the presence of the polyester catalyst described in one of the objects of the present invention or the polyester catalyst obtained by the preparation method described in the second object of the present invention.

[0077] In a preferred embodiment, based on the theoretical weight of the polyester product, the amount of the polyester catalyst used is 10 to 160 ppmw, wherein the amount of the polyester catalyst used is based on the weight of the titanium atoms therein.

[0078] In a further preferred embodiment, the amount of the polyester catalyst used is 20 to 90 ppmw based on the theoretical weight of the polyester (product), wherein the amount of the polyester catalyst used is based on the weight of the titanium atoms therein.

[0079] The theoretical weight of the polyester product refers to the theoretical polyester weight calculated based on the raw materials before the reaction, which is obtained as follows: a dibasic acid and a diol are reacted in a 1:1 ratio, and the weight of the removed water is removed.

[0080] In a preferred embodiment, the preparation method comprises: firstly subjecting a dibasic acid and a diol to an esterification reaction at 200-230°C and normal pressure to 0.5 MPa to obtain a prepolymer, and then subjecting the prepolymer to polycondensation at 230-250°C and a vacuum pressure of less than 150 Pa to obtain the polyester. After the reaction is completed, the prepolymer is pelletized and stored.

[0081] In a further preferred embodiment, the dibasic acid is terephthalic acid, and the diol is butanediol.

[0082] Wherein, the polyester catalyst is added into the reaction system before the esterification reaction starts.

[0083] The fifth object of the present invention is to provide polyester obtained by the preparation method described in the fourth object of the present invention.

[0084] The polyester has an intrinsic viscosity greater than 0.9 dl / g, a b value <3, and an L value >85.

[0085] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0086] Compared with the prior art, the present invention has the following beneficial effects: the catalytic activity of the catalyst prepared by the method of the present invention is maintained to be equivalent to that of tetrabutyl titanate, and the PBT slices prepared by the catalyst have a hue much lower than that of the slices prepared by tetrabutyl titanate, thereby achieving a better technical effect. DETAILED DESCRIPTION

[0087] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0088] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0089] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0090] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0091] In the present invention, the intrinsic viscosity, hue, etc. of polyester are tested by the following methods:

[0092] (1) Intrinsic viscosity: Phenol-tetrachloroethane mixture was used as solvent and measured with an Ubbelohde viscometer at 25°C.

[0093] (2) Hue: After the pellets were treated at 135°C for 1 hour, the Hunter L value (brightness), a value (red-green hue) and b value (yellow-blue hue) were measured using a BYK Gardner color-view automatic colorimeter. The higher the L value, the greater the brightness; the higher the b value, the yellower the polyester chips. For the present invention, it is desirable to pursue a high L value and a low b value.

[0094] [Example 1]

[0095] Preparation of Catalyst A

[0096] In a reactor equipped with a stirrer, a condenser and a thermometer, 540 g (6 mol) of butanediol and 36 g (2 mol) of water were added, and the mixture was stirred at room temperature for 30 minutes. The mixture was heated to 30°C and stirred for 1 hour. Subsequently, 170 g (0.5 mol) of n-butyl titanate was slowly dripped into the reactor. The solution was slightly turbid. After the mixture was heated to 70°C and stirred for 1 hour, 126 g (0.6 mol) of citric acid monohydrate and 30.6 g (0.15 mol) of aluminum acetate were added. The reaction was continued at a reaction temperature of 90°C for 2 hours. Low-boiling substances were extracted to obtain a nearly colorless homogeneous liquid. The heating was turned off, and 18.2 g (0.1 mol) of triethyl phosphate was added and stirred for 1 hour. The titanium content was quantified with butanediol to 3%, which was catalyst A.

[0097] Preparation of polyester

[0098] 600 g of terephthalic acid, 520 g of 1,4-butanediol and catalyst A (based on the amount of polyester produced, the weight of titanium atoms is 80 ppmw) are mixed into a slurry and added into a polymerization kettle for esterification reaction. The esterification temperature is 220°C and the pressure is normal pressure. The water and tetrahydrofuran generated by the reaction are discharged through a rectification device. After the esterification is completed, the system pressure is reduced to less than 100 Pa by vacuum pumping. At the same time, the reaction temperature is gradually increased to 250°C. When the stirring power reaches the requirement, the reaction is stopped. After that, the reaction product is continuously extruded in strips from the bottom of the polymerization kettle, cooled, and pelletized.

[0099] The test results are shown in Table 1.

[0100] [Example 2]

[0101] The polyester was prepared in the same manner as in Example 1 except that the content of aluminum acetate in Catalyst A was changed to 20.4 g (0.1 mol) to obtain Catalyst A'.

[0102] The test results are shown in Table 1.

[0103] [Example 3]

[0104] Polyester was prepared in the same manner as in Example 1, except that the content of aluminum acetate in Catalyst A was changed to 40.8 g (0.2 mol) to obtain Catalyst A".

[0105] The test results are shown in Table 1.

[0106] [Example 4]

[0107] Preparation of Catalyst B

[0108] In a reactor equipped with a stirrer, a condenser and a thermometer, 540 g (6 mol) of butanediol and 36 g (2 mol) of water were added, and the mixture was stirred at room temperature for 30 minutes. Then, 30.6 g (0.15 mol) of aluminum acetate was added, the mixture was heated to 30°C and stirred for 1 hour. Subsequently, 170 g (0.5 mol) of n-butyl titanate was slowly dripped into the reactor, and the solution was slightly turbid. After the mixture was heated to 70°C and stirred for 1 hour, 90 g (1 mol) of lactic acid and 30.6 g (0.15 mol) of aluminum acetate were added. The reaction was continued at a reaction temperature of 90°C for 2 hours. Low-boiling substances were extracted to obtain a nearly colorless homogeneous liquid. The heating was turned off, and 18.2 g (0.1 mol) of triethyl phosphate was added. After stirring for 1 hour, the titanium content was quantified with butanediol to 3%, which was catalyst B.

[0109] The same method as in Example 1 was used to prepare polyester.

[0110] The test results are shown in Table 1.

[0111] [Example 5]

[0112] Preparation of Catalyst C

[0113] In a reactor equipped with a stirrer, a condenser and a thermometer, 540 g (6 mol) of butanediol and 36 g (2 mol) of water were added, stirred at room temperature for 30 minutes, the temperature was raised to 30°C, stirred for 1 hour, and then 170 g (0.5 mol) of n-butyl titanate was slowly dripped into the reactor. The solution was slightly turbid. After the temperature was raised to 70°C and stirred for 1 hour, 126 g (0.6 mol) of citric acid monohydrate and 21.3 g (0.15 mol) of magnesium acetate were added. The reaction was continued at a reaction temperature of 90°C for 2 hours, and low-boiling substances were extracted to obtain a nearly colorless homogeneous liquid. The heating was turned off, and 18.2 g (0.1 mol) of triethyl phosphate was added. After stirring for 1 hour, the titanium content was quantified with butanediol to 3%, which was catalyst C.

[0114] The same method as in Example 1 was used to prepare polyester.

[0115] The test results are shown in Table 1.

[0116] [Example 6]

[0117] The catalyst was prepared in the same manner as in Example 6.

[0118] Preparation of polyester

[0119] 600 g of terephthalic acid, 520 g of 1,4-butanediol and catalyst D (based on the amount of polyester generated, the weight of titanium atoms is 80 ppmw) are mixed into a slurry and added to a polymerization kettle. At the same time, 3 g of aluminum acetate (0.015 mol) is added for esterification reaction. The esterification temperature is 215°C and the pressure is normal pressure. The water and tetrahydrofuran generated by the reaction are discharged through a distillation device. After the esterification is completed, the system pressure is reduced to less than 100 Pa by vacuum, and the reaction temperature is gradually increased to 250°C. When the stirring power reaches the requirement, the reaction is stopped, and then the reaction product is continuously extruded in strips from the bottom of the polymerization kettle, cooled, and pelletized.

[0120] The test results are shown in Table 1.

[0121] [Example 7]

[0122] The catalyst was prepared in the same manner as in Example 6.

[0123] Preparation of polyester

[0124] 600 g of terephthalic acid, 520 g of 1,4-butanediol and catalyst D (based on the amount of polyester produced, the weight of titanium atoms is 80 ppmw) are mixed into a slurry and added to a polymerization kettle. At the same time, 2 g of germanium dioxide (0.02 mol) is added for esterification. The esterification temperature is 225°C and the pressure is normal pressure. The water and tetrahydrofuran generated by the reaction are discharged through a distillation device. After the esterification is completed, the system pressure is reduced to less than 100 Pa by vacuuming. At the same time, the reaction temperature is gradually increased to 250°C. When the stirring power reaches the requirement, the reaction is stopped. After that, the reaction product is continuously extruded in strips from the bottom of the polymerization kettle, cooled, and pelletized.

[0125] The test results are shown in Table 1.

[0126] [Example 8]

[0127] Catalyst preparation

[0128] In a reactor equipped with a stirrer, a condenser and a thermometer, 450.6 g (5 mol) of butanediol and 14 g of water were added, and the mixture was stirred at room temperature for 20 minutes. The mixture was heated to 40°C and stirred for 0.8 hours. Subsequently, 114 g (0.5 mol) of tetraethyl titanate was slowly dripped into the reactor. The solution was slightly turbid. After the mixture was heated to 50°C and stirred for 1.5 hours, 2.5 mol of malic acid monohydrate and 0.5 mol of potassium acetate were added. The reaction was continued at a reaction temperature of 100°C for 3 hours. Low-boiling substances were extracted to obtain a nearly colorless homogeneous liquid. The heating was turned off, 0.5 mol of tributyl phosphate was added and stirred for 1 hour, and then the titanium content was quantified with butanediol to 3% to obtain a catalyst.

[0129] Preparation of polyester

[0130] 600 grams of terephthalic acid, 520 grams of 1,4-butanediol and a catalyst (based on the amount of polyester produced, the weight of the titanium atom is 60ppmw) are mixed into a slurry and added to a polymerization kettle for esterification. The esterification temperature is 223°C and the pressure is normal pressure. The water and tetrahydrofuran generated by the reaction are discharged through a distillation device. After the esterification is completed, the system pressure is reduced to less than 100Pa by vacuum, and the reaction temperature is gradually increased to 250°C. When the stirring power reaches the requirement, the reaction is stopped, and then the reaction product is continuously extruded in strips from the bottom of the polymerization kettle, cooled, and pelletized. The obtained catalyst not only has a low hue, but also is resistant to hydrolysis.

[0131] [Example 9]

[0132] Catalyst preparation

[0133] In a reactor equipped with a stirrer, a condenser and a thermometer, 225 g (2.5 mol) of butanediol and 3 g of water were added, and the mixture was stirred at room temperature for 40 minutes. The mixture was heated to 35°C and stirred for 1.2 hours. Subsequently, 0.5 mol of tetramethyl titanate was slowly dripped into the reactor, and the solution was slightly turbid. After the mixture was heated to 80°C and stirred for 0.5 hour, 0.5 mol of tartaric acid monohydrate and 0.005 mol of stannous octoate were added, and the reaction was continued at a reaction temperature of 60°C for 6 hours. Low-boiling substances were extracted to obtain a nearly colorless homogeneous liquid. The heating was turned off, 0.05 mol of trimethyl phosphate was added and stirred for 1 hour, and then the titanium content was quantified with butanediol to 3% to obtain a catalyst.

[0134] Preparation of polyester

[0135] 600 grams of terephthalic acid, 520 grams of 1,4-butanediol and a catalyst (based on the amount of polyester produced, the weight of the titanium atom is 100ppmw) are mixed into a slurry and added to a polymerization kettle for esterification. The esterification temperature is 224°C and the pressure is normal pressure. The water and tetrahydrofuran generated by the reaction are discharged through a distillation device. After the esterification is completed, the system pressure is vacuumed and reduced to less than 100Pa. At the same time, the reaction temperature gradually rises to 250°C. When the stirring power reaches the requirement, the reaction is stopped. After that, the reaction product is continuously extruded in strips from the bottom of the polymerization kettle, cooled, and pelletized. The obtained catalyst not only has a low hue, but also is resistant to hydrolysis.

[0136] [Comparative Example 1]

[0137] Polyester was prepared in the same manner as in Example 1, except that the catalyst A was changed to tetrabutyl titanate (the weight of titanium atoms was 80 ppmw based on the amount of the produced polyester).

[0138] The test results are shown in Table 1.

[0139] [Comparative Example 2]

[0140] Preparation of Catalyst E

[0141] In a reactor equipped with a stirrer, a condenser and a thermometer, 276 g (6 mol) of anhydrous ethanol and 36 g (2 mol) of water were added, and the mixture was stirred at room temperature for 30 minutes. The mixture was heated to 30°C and stirred for 1 hour. Subsequently, 170 g (0.5 mol) of n-butyl titanate was slowly dripped into the reactor. The solution was slightly turbid. After the mixture was heated to 70°C and stirred for 1 hour, 126 g (0.6 mol) of citric acid monohydrate and 30.6 g (0.15 mol) of aluminum acetate were added. The reaction was continued at a reaction temperature of 90°C for 2 hours. Low-boiling substances were extracted to obtain a nearly colorless homogeneous liquid. The heating was turned off, and 18.2 g (0.1 mol) of triethyl phosphate was added and stirred for 1 hour. The titanium content was quantified with butanediol to 3%, which was catalyst E.

[0142] Preparation of polyester

[0143] 600 g of terephthalic acid, 520 g of 1,4-butanediol and catalyst E (based on the amount of polyester generated, the weight of titanium atoms is 80 ppmw) are mixed into a slurry and added into a polymerization kettle for esterification reaction. The esterification temperature is 200-225°C and the pressure is normal pressure. The water and tetrahydrofuran generated by the reaction are discharged through a distillation device. After the esterification is completed, the system pressure is reduced to less than 100 Pa by vacuum pumping. At the same time, the reaction temperature is gradually increased to 250°C. When the stirring power reaches the requirement, the reaction is stopped. After that, the reaction product is continuously extruded in strips from the bottom of the polymerization kettle, cooled, and pelletized.

[0144] The test results are shown in Table 1.

[0145] [Comparative Example 3]

[0146] Preparation of Catalyst F

[0147] Add 540 g (6 mol) of butanediol to a reactor equipped with a stirrer, a condenser and a thermometer, stir at room temperature for 30 minutes, heat to 30°C, stir for 1 hour, then slowly drop 170 g (0.5 mol) of n-butyl titanate into the reactor, the solution becomes clear, heat to 70°C and stir for 1 hour, add 126 g (0.6 mol) of citric acid monohydrate and 30.6 g (0.15 mol) of aluminum acetate, and continue to react at a reaction temperature of 90°C for 2 hours. Draw out low-boiling substances to obtain a nearly colorless homogeneous liquid, turn off the heating, add 18.2 g (0.1 mol) of triethyl phosphate, stir for 1 hour, and quantify with butanediol until the titanium content is 3%, which is Catalyst F.

[0148] Preparation of polyester

[0149] 600 g of terephthalic acid, 520 g of 1,4-butanediol and catalyst F (based on the amount of polyester generated, the weight of titanium atoms is 80 ppmw) are mixed into a slurry and added into a polymerization kettle for esterification reaction. The esterification temperature is 200-225°C and the pressure is normal pressure. The water and tetrahydrofuran generated by the reaction are discharged through a rectification device. After the esterification is completed, the system pressure is reduced to less than 100 Pa by vacuum pumping. At the same time, the reaction temperature is gradually increased to 250°C. When the stirring power reaches the requirement, the reaction is stopped. After that, the reaction product is continuously extruded in strips from the bottom of the polymerization kettle, cooled and pelletized.

[0150] The test results are shown in Table 1.

[0151] [Comparative Example 4]

[0152] Preparation of Catalyst G

[0153] In a reactor equipped with a stirrer, a condenser and a thermometer, 540 g (6 mol) of butanediol and 36 g (2 mol) of water were added, and the mixture was stirred at room temperature for 30 minutes. The mixture was heated to 30°C and stirred for 1 hour. Subsequently, 126 g (0.6 mol) of citric acid monohydrate was added to the reactor. The mixture was heated to 70°C and stirred for 1 hour. Then, 170 g (0.5 mol) of n-butyl titanate was slowly added dropwise. The solution was slightly turbid. 30.6 g (0.15 mol) of aluminum acetate was continued to react at a reaction temperature of 90°C for 2 hours. Low-boiling substances were extracted to obtain a nearly colorless homogeneous liquid. The heating was turned off, and 18.2 g (0.1 mol) of triethyl phosphate was added and stirred for 1 hour. The titanium content was quantified with butanediol to 3%, which was catalyst G.

[0154] The same method as in Example 1 was used to prepare polyester.

[0155] The test results are shown in Table 1.

[0156] Table 1:

[0157]

[0158] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A polyester catalyst comprising the reaction product of: (1) a reactant I of a diol, water, a titanium compound and an optional metal compound; (2) an organic acid; (3) an optional metal compound; (4) a phosphate ester; wherein: The diol, water, the titanium compound and the optional metal compound are mixed to obtain reactant I; the obtained reactant I is mixed with the organic acid and the optional metal compound to obtain reactant II; the obtained reactant II is mixed with the phosphate ester to obtain the polyester catalyst; the diol is selected from C2 to C 10 The titanium compound is selected from alkoxy titanate, represented by Ti(OR)4, wherein R is selected from C1~C 10 The straight-chain or branched hydrocarbon group is selected from aliphatic organic acids and / or aromatic organic acids, the metal compound is selected from at least one of compounds containing Group IA elements, compounds containing Group IIA elements, compounds containing Group IIIA elements, and compounds containing Group IVA elements; the phosphate ester is selected from organic phosphate esters; based on the total weight of the diol and water as 100wt%, the amount of water is 0.1wt%~10wt%; the molar ratio of the diol to the titanium compound is (1-15):1; the molar ratio of the organic acid to the titanium compound is (0.1-18):1; the molar ratio of the metal compound to the titanium compound is (0.01-2):1; the molar ratio of the phosphate ester to the titanium compound is (0.1-4):

1.

2. The polyester catalyst according to claim 1, characterized in that The dihydric alcohol is selected from C2 to C8 dihydric organic alcohols; and / or The titanium compound is selected from alkoxy titanate, represented by Ti(OR)4, wherein R is a straight chain or branched hydrocarbon group selected from C1 to C8.

3. The polyester catalyst according to claim 1, characterized in that The diol is at least one selected from 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, pentanediol, ethylene glycol, 1,6-hexanediol, 1,4-cyclohexanedimethanol and diethylene glycol; and / or The titanium compound is at least one selected from tetramethyl titanate, tetraethyl titanate, tetraethylhexyl titanate, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, and tetraisooctyl titanate.

4. The polyester catalyst according to claim 1, characterized in that The molar ratio of the diol to the titanium compound is (5-12):

1.

5. The polyester catalyst according to claim 1, characterized in that Based on 100wt% of the total weight of diol and water, the amount of water used is 0.1wt%~5wt%.

6. The polyester catalyst according to claim 1, characterized in that The organic acid is selected from at least one of tartaric acid, oxalic acid, malic acid, citric acid, salicylic acid, lactic acid and glycolic acid.

7. The polyester catalyst according to claim 1, characterized in that The molar ratio of the organic acid to the titanium compound is (0.1-5):

1.

8. The polyester catalyst according to claim 1, characterized in that The metal compound is selected from at least one of a sodium-containing compound, a lithium-containing compound, a calcium-containing compound, an aluminum-containing compound, a germanium-containing compound and a tin-containing compound.

9. The polyester catalyst according to claim 1, characterized in that The molar ratio of the metal compound to the titanium compound is (0.01-1):

1.

10. The polyester catalyst according to claim 1, characterized in that The phosphate ester is selected from at least one of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate and triphenyl phosphate.

11. The polyester catalyst according to claim 1, characterized in that The molar ratio of the phosphate ester to the titanium compound is (0.1-2):

1.

12. The polyester catalyst according to any one of claims 1 to 11, characterized in that The reactant I is obtained at 40-100°C; and / or The reactant I, an organic acid, an optional metal compound and a phosphoric acid ester are reacted at 10 to 100° C. for 0.5 to 10 hours to obtain the catalyst.

13. The polyester catalyst according to claim 12, characterized in that Reactant I is obtained at 50-80°C; and / or The reactant I, an organic acid, an optional metal compound and a phosphoric acid ester are reacted at 10 to 90° C. for 2 to 6 hours to obtain the catalyst.

14. A method for preparing the polyester catalyst according to any one of claims 1 to 13, comprising: Step 1, mixing the diol, water, the titanium compound and the optional metal compound to obtain reactant I; Step 2: Mix the obtained reactant I with the organic acid and the optional metal compound to obtain reactant II through reaction; Step 3: Mix the obtained reactant II with the phosphate ester to obtain the polyester catalyst through reaction; the diol is selected from C2 to C 10 The titanium compound is selected from alkoxy titanate, represented by Ti(OR)4, wherein R is selected from C1~C 10 The straight-chain or branched hydrocarbon group is selected from aliphatic organic acids and / or aromatic organic acids, the metal compound is selected from at least one of compounds containing Group IA elements, compounds containing Group IIA elements, compounds containing Group IIIA elements, and compounds containing Group IVA elements; the phosphate ester is selected from organic phosphate esters; based on the total weight of the diol and water as 100wt%, the amount of water is 0.1wt%~10wt%; the molar ratio of the diol to the titanium compound is (1-15):1; the molar ratio of the organic acid to the titanium compound is (0.1-18):1; the molar ratio of the metal compound to the titanium compound is (0.01-2):1; the molar ratio of the phosphate ester to the titanium compound is (0.1-4):

1.

15. The preparation method according to claim 14, characterized in that The dihydric alcohol is selected from C2 to C8 dihydric organic alcohols; and / or The titanium compound is selected from alkoxy titanate, represented by Ti(OR)4, wherein R is a straight chain or branched hydrocarbon group selected from C1 to C8; and / or The organic acid is at least one selected from tartaric acid, oxalic acid, malic acid, citric acid, salicylic acid, lactic acid, and glycolic acid; and / or The metal compound is selected from at least one of a sodium-containing compound, a lithium-containing compound, a calcium-containing compound, an aluminum-containing compound, a germanium-containing compound and a tin-containing compound; and / or The phosphate ester is selected from at least one of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate or triphenyl phosphate.

16. The preparation method according to claim 14, characterized in that: The diol is at least one selected from 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, pentanediol, ethylene glycol, 1,6-hexanediol, 1,4-cyclohexanedimethanol and diethylene glycol; and / or The titanium compound is at least one selected from tetramethyl titanate, tetraethyl titanate, tetraethylhexyl titanate, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, and tetraisooctyl titanate.

17. The preparation method according to claim 14, characterized in that: Based on 100wt% of the total weight of diol and water, the amount of water is 0.1wt% to 5wt%; and / or The molar ratio of the diol to the titanium compound is (5-12):1; and / or The molar ratio of the organic acid to the titanium compound is (0.1-5):1; and / or The molar ratio of the metal compound to the titanium compound is (0.01-1):1; and / or The molar ratio of the phosphate ester to the titanium compound is (0.1-2):

1.

18. The preparation method according to claim 14, characterized in that: Step 1 at 40-100°C; and / or Step 2 is performed at 10-100° C. for 0.5-10 hours.

19. The preparation method according to claim 14, characterized in that: Step 1 is carried out at 50-80°C; and / or Step 2 is carried out at 10-90°C for 2-6 hours.

20. Use of the polyester catalyst according to any one of claims 1 to 13 or the polyester catalyst obtained by the preparation method according to any one of claims 14 to 19 in the preparation of polyester.

21. The use according to claim 20, characterized in that Used in low-hue polybutylene terephthalate resin applications.

22. A method for preparing polyester, the method comprising: The process is carried out using dibasic acid and diol as raw materials in the presence of the polyester catalyst according to any one of claims 1 to 13 or the polyester catalyst obtained by the preparation method according to any one of claims 14 to 19.

23. The preparation method according to claim 22, characterized in that: Based on the theoretical weight of the polyester product, the amount of the polyester catalyst used is 10 to 160 ppmw, wherein the amount of the polyester catalyst used is calculated based on the weight of the titanium atoms therein.

24. The preparation method according to claim 22, characterized in that: The preparation method comprises: firstly subjecting a dibasic acid and a diol to an esterification reaction at 200-230°C and normal pressure-0.5MPa to obtain a prepolymer, and then subjecting the prepolymer to polycondensation at 230-250°C and a vacuum pressure less than 150Pa to obtain the polyester.

Citation Information

Patent Citations

  • Polybutylene terephthalate and process for production thereof

    CN101253217A

  • Preparation method of high crystallization thermoplastics type polybutylene terephthalate slice

    CN101824143A

  • Continuous catalysis production method of PBT resin

    CN105085873A

  • Catalyst and process

    CN1720216A

  • Titanium polyester catalyst for preparing polyester

    CN101942078A